Reactions of the American Jews to Trump’s Jerusalem Embassy Move: Continuation of the Historical Pattern? - Yavuz, Hamza; Okur, Mehmet Akif (SAGE Publications, 2018)
Pro-Israeli politicians in Washington have long supported the relocation of the U.S. Embassy from Tel Aviv to Jerusalem. Nevertheless, contrary to the widespread belief, not all American Jews offer unconditional support to U.S. decisions taken in order to promote Israel’s national interests. In this article, interviews were conducted with representatives from various Jewish diaspora groups in United States shortly before and after the official declaration of the U.S. Embassy move in December 2017. This article documents that opinions of American Jews diverge significantly regarding Trump’s Jerusalem Embassy decision. This article argues that this divergence stems from Israel’s actions and policies toward the Palestinians since the late 1970s and political and religious divisions within the American Jewish community.
Keywords: 16. Peace & justice